Reply to the comments on “Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust” - Wang, R.; Collins, William; Weinberg, R.; Richards, J.; He, W. (Springer, 2017)
Stepanov et al. (Contrib Mineral Petrol, 2017) question our conclusion that the UPVs in southern Tibet were derived by partial melting of an old, metasomatized subcontinental lithospheric mantle (SCLM) of the subducted Indian plate. Instead, they propose that these ultrapotassic volcanic rocks (UPVs) are shoshonitic and were generated in two steps: direct melting of crustal rocks first, and then the melts interacted with mantle peridotite. However, the trace element, isotopic, thermal, structural, and seismic evidence is consistent with the xenolith evidence (Wang et al in Contrib Mineral Petrol 172:62, 2016) for hybridisation of ascending Indian subcontinental lithospheric mantle-derived UPV magmas with the deep, isotopically unevolved, Tibetan crust. This necessitates a model whereby partial melting of subducting Indian SCLM generates the UPV suite of southern Tibet.